Biology of Gratiana boliviana, the First Biocontrol Agent Released to Control Tropical Soda Apple in the USA - Julio C. Medal; D. Gandolfo; James P. Cuda (EDIS)
Tropical soda apple (TSA), Solanum viarum Dunal (Solanaceae), is a perennial weed, native to South America, that has spreading throughout Florida at an alarming rate during the last decade. TSA was first reported in Glades County in 1988. This weed is also present in Alabama, Arkansas, Georgia, Louisiana, Mississippi, North Carolina, Pennsylvania, South Carolina, Tennessee, and Texas. Currently, the area infested with TSA is estimated at more than one million acres. This document is ENY-826, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: November 2003.